Comparative analysis of ureteroileal anastomotic stricture rates: Bricker versus Wallace techniques in ileal conduit urinary diversion—a single-surgeon study with BMI-matched design and long-term follow-up excluding cancer recurrence bias - Ren, Chao; Xiao, Maolin; Zhu, Jie; Tong, Wei; Yi, Faxian (Frontiers in Oncology, 2025)
BackgroundUreteroileal anastomotic stricture (UIAS) remains a critical complication following ileal conduit urinary diversion for muscle-invasive bladder cancer (MIBC). Despite widespread use of Bricker and Wallace techniques, comparative outcomes remain debated. This study compares stricture rates between these techniques under standardized surgical conditions, controlling for body habitus and without cancer recurrence-related stenosis.MethodsA retrospective analysis included 46 patients undergoing laparoscopic ileal conduit diversion by a single surgeon (2017–2021). Patients were stratified into Bricker (n=18) and Wallace (n=28) groups, matched for BMI and comorbidities. Hydronephrosis severity was graded using the Onen system. Statistical analyses utilized Fisher’s exact test, Mann-Whitney U test, and t-test.ResultsNo significant difference in hydronephrosis incidence was observed (Bricker: 11.1% vs. Wallace: 0%, p=0.148). However, the Bricker group exhibited longer operative time (301.89 ± 11.76 vs. 281.32 ± 10.15 minutes, p<0.001) and hospitalization duration (18.18 ± 8.22 vs. 11.38 ± 5.11 days, p=0.005). All strictures were asymptomatic (Onen Grade 1).ConclusionBoth techniques demonstrate comparable safety regarding stricture rates. Wallace anastomosis offers superior operative efficiency, while Bricker requires additional time for technical precision. This study highlights the importance of standardized surgical protocols and long-term surveillance in optimizing urinary diversion outcomes.